Effect of aflatoxin B1 exposure on the progression of depressive-like behavior in rats - Subramaniam, Syarminie; Sabran, Mohd-Redzwan; Stanslas, Johnson; Kirby, Brian P. (Frontiers Media, 2022)
While it is well documented that aflatoxin B1 (AFB1); one of the most toxic food contaminants is linked to the development of depression. However, the mechanism on how it affects the gut and brain health leading to depressive-like behavior remains unclear. This study was conducted to determine the effect of AFB1 on the progression of depressive-like behavior. Thirty-two (n = 32) male Sprague Dawley rats were randomly allocated into four groups: control, low-dose (5 μg AFB1/kg), high-dose (25 μg AFB1/kg) and positive control group; exposed on chronic unpredictable mild stress (CUMS). After 4 weeks of exposure, sucrose preference test (SPT) and force swim test (FST) were used to measure behavioral despair. Fecal samples were selectively cultured to profile the bacteria. Body weight and relative organs weights were compared among groups. AFB1 and CUMS caused reduction in body weight and food intake as well as increased relative weight of adrenal glands, liver, and brain. Rats in AFB1 and CUMS groups had suppressed sucrose preference and prolonged immobility time in FST, wherein this could indicate anhedonia. Besides, fecal count of Lactobacillus spp. was significantly low following AFB1 exposure, with increasing count of Bifidobacterium spp, in comparison to the control. Indeed, further biochemical analysis and metagenomic approach are warranted to explore the underlying mechanisms on the role of gut microbiota dysbiosis and dysregulation of gut-brain axis due to AFB1 neurotoxicity on the progression of depressive-like behavior.